2018
DOI: 10.1021/acs.jafc.8b02899
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Hydrogel Properties of pH-Sensitive Amphoteric Chitin Nanocrystals

Abstract: Different from single charged or uncharged nanocrystals, amphoteric chitin nanocrystals (A-ChNCs) with both amine and carboxylate groups prepared with 2,2,6,6-tetramethylpiperidine-1-oxy-radical (TEMPO)-mediated oxidation and partial deacetylation were individually nanodispersed by sonicating in water at pH 3 and pH 11. The effects of the amount of NaClO2 added in TEMPO-oxidation, deacetylation time, and sequence of the two treatments on the weight recovery ratios of the A-ChNCs were investigated. The A-ChNCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“… 240 , 346 Deacetylation of TEMPO-oxidized chitin or TEMPO-mediated oxidation of partially deacetylated chitin yields ChNC with both amine and carboxyl groups, which are amphoteric and zwitterionic. 361 , 362 The obtained ChNC is stable in alkaline and acidic conditions and can interact due to their amphoteric character with both cationic and anionic dyes or other species.…”
Section: Deconstruction and Modification Of Biopolymers And Biocolloidsmentioning
confidence: 99%
“… 240 , 346 Deacetylation of TEMPO-oxidized chitin or TEMPO-mediated oxidation of partially deacetylated chitin yields ChNC with both amine and carboxyl groups, which are amphoteric and zwitterionic. 361 , 362 The obtained ChNC is stable in alkaline and acidic conditions and can interact due to their amphoteric character with both cationic and anionic dyes or other species.…”
Section: Deconstruction and Modification Of Biopolymers And Biocolloidsmentioning
confidence: 99%
“…9 Furthermore, partial deacetylation with TEMPO-oxidation was shown to result in amphoteric ChNCs. 219,231 Ammonium persulfate is another oxidant that can be used for ChNC isolation, 217 usually ending up with a higher charge than with TEMPObased ChNCs. 216 Surveying a completely different bottom-up approach, Kadokawa et al 222 found that chitin regenerated from an ionic liquid can reassemble into a whisker form when the resulting chitin-ionic liquid gel is soaked in methanol.…”
Section: Biomacromoleculesmentioning
confidence: 99%
“…Chitin was suspended in sodium phosphate buffer (pH = 6.86) containing a certain amount of TEMPO, NaClO 2 , and NaClO, and the chitin nanofibers were obtained by oxidation under certain conditions. Jiang et al [ 82 ] prepared chitin nanocrystals with a length of 200–600 nm and a width of 6–15 nm by a similar method using TEMPO/NaClO 2 /NaClO system at pH = 6.8.…”
Section: Preparation Methods Of Nano‐chitinmentioning
confidence: 99%